CORPUS DEVELOPMENT AND AUTOMATIC ANNOTATION SYSTEMS IN ENGLISH AND UZBEK: STRUCTURAL AND FUNCTIONAL ASPECTS - Abdusalomov Doniyor Tog‘ayali o‘g‘li (Western European Studies, 2025)
This article examines the creation of text corpora in English and Uzbek, the implementation of automatic annotation systems, and their structural and functional underpinnings. The study covers existing corpus-building technologies, such as tokenization, morphological analysis, syntactic parsing, and semantic tagging, paying special attention to the adaptation needed for the Uzbek language. It further explores modern trends in automatic annotation (e.g., artificial intelligence, machine learning) and addresses the technical and methodological challenges associated with building corpora and comparing linguistic parameters in English and Uzbek. Based on the results, recommendations for further research and practical application are proposed.
Keywords: corpus linguistics; English; Uzbek